Microwave-Assisted Solvothermal Liquefaction of Kenaf Stalks for Bio-oil Production - Ramli, A. (Springer Science and Business Media B.V., 2021)
In this study, microwave-assisted solvothermal liquefaction was investigated to produce bio-oil from Kenaf stalks. Optimization of process parameters was performed using concentrated sulfuric acid as catalyst at biomass to solvent ratio of 1:10, catalyst loading of 10 and microwave power of 300Â W with constant stirring at 200Â rpm. The maximum bio-oil yield of 87 was achieved at temperature of 180Â Â°C for duration of 20Â min, in which ethanol was used as solvent. Different types of catalysts were also tested to produce bio-oil at the optimum process conditions. It was found that synthesized ionic liquid BMIMCl catalyst could give the highest quality of bio-oil in terms of heating value (26.55Â MJ/kg) with considerable bio-oil yield. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.